Effect of supplementation with polyphenol extract of Thymus atlanticus on paraoxonase‐1 activity, insulin resistance, and lipid profile in high‐fat diet‐fed hamsters. Issue 9 (16th May 2022) - Khouya, Tarik; Ramchoun, Mhamed; Hmidani, Abdelbassat; Amrani, Souliman; Benlyas, Mohamed; Kasbi Chadli, Fatima; Ouguerram, Khadija; Alem, Chakib
Abstract: Thymus atlanticus has been used by Moroccan people to treat a variety of health problems, particularly metabolic disorders. In this study, hamsters fed a high‐fat diet daily received distilled water (a positive control) or a single dose of Thymus atlanticus polyphenols (Pp) for 63 days. The negative control was fed a normal diet and received distilled water. Results showed that the supplementation of HFD with Pp significantly ( p < .001) reduced the levels of MDA and LDL cholesterol, restored insulin level, and increased the activities of serum paraoxonase‐1 and HDL cholesterol levels, but did not affect ( p > .05) the activity of superoxide dismutase and glutathione peroxidase when compared with the group feeding HFD alone. Thymus atlanticus could be an effective agent against dyslipidemia, oxidative stress, and insulin resistance. Practical applications: HFD consumption is a risk factor for oxidative stress and the development of metabolic disorders, such as hyperlipidemia and insulin resistance, which may result in atherosclerosis and related cardiovascular diseases, the leading causes of death globally. The management of these alterations is an important strategy to prevent and treat heart complications. Our results showed that T. atlanticus effectively alleviated HFD‐induced hyperlipidemia and insulin resistance and improved PON1 activity. T. atlanticus is a source of biomolecules that may be an effective supplement for controlling HFD‐related metabolic disorders. Therefore, the findings of this study may be helpful in the preparation of effective supplements from T. atlanticus to control metabolic disorders and related complications. Abstract : Sixty‐three days of supplementation with a polyphenol‐rich extract from Thymus atlanticus prevented diabetes, hyperlipidemia, and oxidative stress induced by a high‐fat diet (HFD) in hamsters via improving insulin signaling, decreasing the levels of LDL cholesterol and VLDL triglycerides, increasing HDL cholesterol level, and enhancing serum paraoxonase‐1 activity.